The Implementation of Building Information Modelling for Cut and Fill Quantity Takeoff in Toll Road Project - Fahmilia, Astuti; Isvara, Wisnu (Jurnal Indonesia Sosial Sains, 2023)
Technology has been going rapidly through the years, and BIM is one of the massive developments that offer some benefits for the construction industry. BIM is widely used in building project and has started to be used in infrastructure projects such as toll roads. In a toll road project, cut and fill is one of the massive volumes, which consume a lot of time to calculate the quantity and has a high chance to human error. This research aims to determine the implementation of BIM in cut and fill quantity take-off in Toll Road Project. The methodology for this research is qualitative descriptive with in-depth interviews with the expert. The study shows that implementing quantity take-off with BIM increases accuracy, reduces time, minimizes human error and efficiency. Nevertheless, still have some lacks, such as expensive cost for siftware, hardware and training, needs a long time adaptation to the organization, and also need collaboration all of the stakeholder to succesfuly implement BIM